Correlación entre hallazgos de hábitos en higiene bucal y estado de salud oral en la población escolar de corpoadases (Corporación alianza para el desarrollo ambiental, social y económico sostenible). - Díaz Mejía, Marguerith; Pinilla Quintero, Nathalia Alexandra; Rodríguez Quiroga, Arelis (Universidad Antonio Nariño, 2021)
Background: In the city of Bucaramanga there are sectors in a vulnerable situation, in which it is necessary to continuously evaluate the state of oral health and the habits and practices related to it. Objective: To know the oral hygiene habits and compare them with the bacterial plaque index and the presence of caries, in the school population of the Colombian Institute of Family Welfare ICBF, Corpoadases externado.